2020
DOI: 10.1111/pace.13990
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation post central retinal artery occlusion: Role of implantable loop recorders

Abstract: Objective This study evaluated the risk of subclinical atrial fibrillation (AF) in patients with central retinal artery occlusion (CRAO) compared to those with cryptogenic stroke using implantable loop recorders (ILR). Methods We conducted a retrospective analysis of 273 consecutive patients who had ILRs inserted at our institution for either cryptogenic stroke (n = 227) or CRAO (n = 46). Our primary endpoint was a time to event analysis for the new diagnosis of AF by ILR. Univariable and multivariable Cox pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…AF was a cause of CRAO. A previous study using implantable loop recorders reported that 15% of CRAO patients had subclinical AF 8 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…AF was a cause of CRAO. A previous study using implantable loop recorders reported that 15% of CRAO patients had subclinical AF 8 …”
Section: Discussionmentioning
confidence: 98%
“…A previous study using implantable loop recorders reported that 15% of CRAO patients had subclinical AF. 8 There have been few reports of ophthalmic complications of AF ablation. Although a previous study showed one patient developed a unilateral quadrantanopsia consistent with a retinal artery embolus after catheter ablation, 9 there have been no reports about CRAO with complete unilateral visual loss.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using implantable loop recorders reported that 15% of CRAO patients had subclinical AF. 8 There have been few reports of ophthalmic complications of AF ablation. Although a previous study showed one patient developed a unilateral quadrantopsia consistent with a retinal artery embolus after catheter ablation, 9 there have been no reports about CRAO with complete unilateral visual loss.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, RAO is a consequence of an embolism originating from atherosclerotic plaques in the ipsilateral carotid artery, heart, or aortic arch [4,8]. Recently, the role of cardiac arrhythmias in the aetiology of RAO has also been receiving increasing attention [9][10][11][12][13][14][15][16]. Results of previous studies concerning the relationship between RAO and AF indicate that there is a correlation between AF and RAO.…”
Section: Atrial Fibrillation As One Of the Causes Of Raomentioning
confidence: 99%
“…Watson et al [13] used implantable event recorders to evaluate the risk of subclinical AF in patients with CRAO, compared to patients with cryptogenic stroke. The study revealed that the incidence of subclinical AF in CRAO patients was similar to that observed in the cryptogenic stroke group.…”
Section: Cardiological Diagnostic Evaluation Of Patients With Raomentioning
confidence: 99%